Development of a real-time aided inertia navigation system for an underwater robotic vehicle - Mohammad, Dzulkifli Mohyi Hapipi (2008)
This thesis explores the development on an Aided Inertial Navigation System (AINS) for a compact, low cost twin-barrel URV developed by the Mechanical and Production Engineering (MPE) department of Nanyang Technological University (NTU), Singapore. This system uses low cost sensors, which produce large drifts and bias errors. Low cost sensors have errors up to 1000 times larger than high cost precision sensors. The URV utilises the IMU600CA-200 inertial sensor from Crossbow and is aided by non-inertial sensors such as Argonaut MD Velocity Doppler from Sontek, KVH compass, Tritech Altimeter, Crossbow Tilt sensor, Sonavision scanning sonar and Falmouth pressure sensor. Relying of the fast update rate of the IMU, the additional sensors aids the IMU by correct the vehicle states at periodic interval. All the data processing had to be done by an onboard Octagon microcomputer running at 133 MHz. For optimal performance, QNX 4.25 operating system was used to enable real time processing for the sensors. For the navigation system to function as required, the sensors, computer hardware and operating system need to be optimally configured.